Antenna array control system with combination of strength and flexible scanning programs - Larisa V. Vinnik; Sergey E. Mishchenko (Физика волновых процессов и радиотехнические системы, 2022)
The structure of the antenna array control system with a combination of strengh and flexible scanning programs is proposed, characterized by the introduction of additional modules of statistics and expert assessments in the feedback circuit between the secondary processing module and hardware and software complexes for the formation of transmitting and receiving antenna array radiation patterns. The implementation of this structure allows for the formation of an additional transmitting and several receiving beams to confirm marks that do not meet the specified detection criterion. An algorithm for controlling an active phased array antenna has been developed, characterized by a procedure for additional confirmation of marks with a low signal-to-noise ratio due to the formation of additional transmitting and receiving beams. The estimates of the gain from the implementation of the proposed structural scheme of the antenna array control system and the algorithm of its functioning are obtained.